Virtualization for dummies - Golden, Bernard (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2007)
A guide to virtualization covers such topics as server virtualization, managing a virtualization project, software options, using VMware Server, and implementing XenExpress.
Fakulti Keusahawanan & Perniagaan.
Includes index.
Keywords: Virtual storage (Computer science)